2019
DOI: 10.1186/s13071-019-3509-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of large-scale mosquito densovirus production by in vivo methods

Abstract: Background Mosquito-borne diseases (MBDs) cause a significant proportion of the global infectious disease burden. Vector control remains the primary strategy available to reduce the transmission of MBDs. However, long-term, wide-scale and large-scale traditional chemical pesticide application has caused significant and increased negative effects on ecosystems and broader emerging insecticide resistance in vectors; therefore, the development of a novel alternative approach is urgently needed. Mosqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Once mosquitoes become infected with mosquito-specific viruses, they are transferred to the aquatic environment during oviposition and replicate in the larval bodies. MDVs actively replicate in the larval bodies [ 47 ] and larvae shed viral particles through excretion in the aquatic environment [ 48 ]. The AalDV-5 viral titer in the AalDV-5+ Bti -exposed larvae and larval rearing water remained high for a longer time than that of the AalDV-5 oil in both semi- and open-field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Once mosquitoes become infected with mosquito-specific viruses, they are transferred to the aquatic environment during oviposition and replicate in the larval bodies. MDVs actively replicate in the larval bodies [ 47 ] and larvae shed viral particles through excretion in the aquatic environment [ 48 ]. The AalDV-5 viral titer in the AalDV-5+ Bti -exposed larvae and larval rearing water remained high for a longer time than that of the AalDV-5 oil in both semi- and open-field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant viruses replicated significantly in rearing water, similar to the replication of wt-AeDNV. The increase in viral concentration showed that the infected larvae released viral particles into the water environment, which facilitated the horizontal transmission of the virus [65]. The recombinant viral packaging is stable, allows for secondary virus transmission, and increases the viral titer in the water through infected larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that a phylogenetic signal linked to w Pip was absent in these sites pointed that the CpDV– Wolbachia vertical cotransmission is not the major force driving the CpDV distribution and suggests (a) the horizontal transmission of CpDV between larvae, (b) transmission of CpDV paternally or venereally from fathers to offspring, in contrast to maternally transmitted Wolbachia , and (c) putative rare occurrence of horizontal transfers of Wolbachia . Horizontal transmission during the larval stage has been experimentally demonstrated for several mosquito densoviruses and thought to be the main transmission mode for these viruses (Ledermann, Suchman, Black, & Carlson, 2004; Li et al., 2019; Sun et al., 2019), although this has not yet been experimentally shown for CpDV. Venereal transmission from infected males to females has also previously been shown for Aedes albopictus densovirus at very low frequency (Barreau et al., 1997), although whether mosquito densoviruses can also be paternally transmitted remains unknown.…”
Section: Discussionmentioning
confidence: 99%